Development of an orthotopic syngeneic murine model of colorectal cancer for use in translational research. (December 2019) - Evans, Jonathan P; Winiarski, Boleslaw K; Sutton, Paul A; Ressel, Lorenzo; Duckworth, Carrie A; Pritchard, D Mark; Palmer, Daniel H; Goldring, Christopher E; Kitteringham, Neil R
Improving outcomes in colorectal cancer requires more accurate in vivo modelling of the disease in humans, allowing more reliable pre-clinical assessment of potential therapies. Novel imaging techniques are necessary to improve the longitudinal assessment of disease burden in these models, reducing the number of animals required for translational studies. This report describes the development of an immune-competent syngeneic orthotopic murine model of colorectal cancer, utilising caecal implantation of CT26 cells stably transfected with the luciferase gene into immune-competent BALB/c mice, allowing serial bioluminescent imaging of cancer progression. Luminescence in the stably transfected CT26 cell line, after pre-conditioning in the flank of a BALB/c mouse, accurately reflected cell viability and resulted in primary caecal tumours in five of eight (63%) mice in the initial pilot study following caecal injection. Luminescent signal continued to increase throughout the study period with one mouse (20%) developing a liver metastasis. Histopathological assessment confirmed tumours to be consistent with a poorly differentiated adenocarcinoma. We have now performed this technique in 68 immune-competent BALB/c mice. There have been no complications from the procedure or peri-operative deaths, with primary tumours developing in 44 (65%) mice and liver metastases in nine (20%) of these. This technique provides an accurate model of colorectal cancer with tumours developing in the correct microenvironment and metastasising to the liver with a similar frequency to that seen in patients presenting with colorectal cancer, with serial bioluminescent reducing the murine numbers required in studies by removing the need for cull for assessment of disease burden.